2023
DOI: 10.1101/2023.12.22.23300425
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Plasmodium vivaxgenomic surveillance in the Peruvian Amazon with Pv AmpliSeq assay

Johanna Helena Kattenberg,
Luis Cabrera-Sosa,
Erick Figueroa-Idelfonso
et al.

Abstract: BackgroundPlasmodium vivaxis the most predominant malaria species in Latin America, constituting 71.5% of malaria cases in 2021. With several countries aiming for malaria elimination, it is crucial to prioritize effectiveness of national control programs by optimizing the utilization of available resources and strategically implementing necessary changes. To support this, there is a need for innovative approaches such as genomic surveillance tools that can investigate changes in transmission intensity, importe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
26
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(29 citation statements)
references
References 57 publications
2
26
1
Order By: Relevance
“…Using Ampliseq, our team reported Pf lineages with low genetic diversity, double pfhrp2/3 deletion, and resistance haplotypes, except for ART, predominant after 2014 11 . In addition, we showed that Pv transmission is heterogeneous in different settings in the Peruvian Amazon, with high diversity in areas close to Loreto and lower diversity in border areas 13 . However, our molecular surveillance studies mainly focus on urban areas or accessible rural communities.…”
Section: Introductionmentioning
confidence: 84%
See 4 more Smart Citations
“…Using Ampliseq, our team reported Pf lineages with low genetic diversity, double pfhrp2/3 deletion, and resistance haplotypes, except for ART, predominant after 2014 11 . In addition, we showed that Pv transmission is heterogeneous in different settings in the Peruvian Amazon, with high diversity in areas close to Loreto and lower diversity in border areas 13 . However, our molecular surveillance studies mainly focus on urban areas or accessible rural communities.…”
Section: Introductionmentioning
confidence: 84%
“…Pv and Pf AmpliSeq Peru library preparation was performed as previously described 11,13,26 using the AmpliSeq Library PLUS kit (Illumina). Brie y, each sample (7.5 µl of DNA) was ampli ed by PCR using two different sets of primer panels.…”
Section: Ampliseq Assaysmentioning
confidence: 99%
See 3 more Smart Citations